Musical and cognitive abilities in children from disadvantaged backgrounds - Boal-Palheiros, G. (2022)
Human beings are born with several abilities which are amenable to change. A growing number of studies have focused on the relations between musical and cognitive abilities but research with children from disadvantaged communities is scarce. This study explored the relations between musical and cognitive abilities in disadvantaged children. Participants were 169 children from deprived neighborhoods, attending the second year of primary education in public schools that do not offer music education. Children’s musical abilities (perception) were measured with the Melody, Rhythm, and Memory tests of Montreal Battery for the Evaluation of Musical Abilities and their cognitive abilities, with five WISC-III subtests (Similarities, Vocabulary, Cubes, Picture Arrangement, and Digits). Parental level of education was obtained from a questionnaire on the socio-economic status of children’s families. Results revealed (1) few and weak correlations between musical and cognitive abilities; (2) stronger correlations of Socioeconomic Status (SES) with cognitive than with musical abilities; (3) digit span predicts all musical abilities; 4) a clear factorial distinction between musical and cognitive abilities. Overall, results suggest that disadvantaged children’s musical and cognitive abilities, as measured by the present instruments, are partly independent regarding processing components.